Interpreting and Negotiating Licensing Agreements: A Guidebook for the Library, Research, and Teaching Professions - Bielefield, Arlene; Cheeseman, Lawrence (Neal-Schuman Publishers, 1999)
Keywords: Handbooks; manuals; etc; Handbooks; manuals; etc; Teachers; License agreements; Popular works; Librarians; United States; dept.ils; faculty_collection

The School Library Media Center - Prostano, Emanuel T.; Prostano, Joyce S. (Libraries Unlimited, 1999)
Keywords: School libraries; United States; United States; Instructional materials centers; dept.ils; faculty_collection

A longitudinal study of emotion expression and personality relations in early development - Abe, J.A.A.; Izard, C.E. (Journal of Personality and Social Psychology, 1999)
To investigate emotion expression and personality relations, the authors coded infants' full-face and component positive and negative expressions during Episodes 4 through 8 of the strange situation procedure at age 18 months and obtained maternal ratings of the 5-factor model of personality when children were 3.5 years old. Full-face negative expression was directly related to Neuroticism and inversely related to Agreeableness and Conscientiousness. By contrast, component positive expression showed the exact opposite pattern of relations. Full-face positive expression was positively correlated with Extraversion and Openness to Experience. These findings indicate that full-face and component expressions may index different intensities of emotions. Emotion expression and personality relations were not mediated by the security of attachment continuum or the emotional reactivity dichotomy derived from the attachment subclassifications.
58 citations (Crossref) [2023-10-31]
Keywords: *Emotions; *Personality; Age Factors; Child; Preschool; Emotions; Female; Humans; Longitudinal Studies; Male; Personality; age; article; dept.ils; dept.psy; emotion; female; human; longitudinal study; male; personality; preschool child

The developmental functions of emotions: An analysis in terms of differential emotions theory - Abe, J.A.A.; Izard, C.E. (Cognition and Emotion, 1999)
A substantial body of theoretical literature testifies to the evolutionary functions of emotions. Relatively little has been written about their developmental functions. This article discusses the developmental functions of emotions from the perspective of differential emotions theory (DET; Izard, 1977, 1991). According to DET, although all the emotions retain their adaptive and motivational functions across the lifespan, different sets of emotions may become relatively more prominent in the different stages of life as they serve stage-related developmental processes. In the first section, we present a brief overview of relevant aspects of the theory. In the second section, we discuss how emotions play a central role in helping the individual achieve developmental milestones and tasks during four major periods of life: Infancy, toddler through preschool years, middle to late childhood, and adolescence. The underlying thesis of this article is that emotions play a central role in stimulating social cognitive attainments at each stage of development. © 1999 Psychology Press Ltd.
69 citations (Crossref) [2023-10-31]
Keywords: dept.ils

Knowledge, concepts, and categories. - Brown, ME (Library & Information Science Research, 1999)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000079397400012
Keywords: dept.ils